Kenali sahabatmu dekati musuhmu : what is the purpose of "you" making friendship? / Maulana Zulfian R; penyunting, Sony Adams - MAULANA ZULFIAN R; SONY ADAMS (Psikologi Corner, 2017)
224 hlm. : ilus. ; 20 cm.